Synestezja a sztuka, red. Aleksandra Rogowska, Julia Kaleńska-Rodzaj - Chełkowska-Zacharewicz, Maria (Res Facta Nova, 2018)
Tekst jest recenzją książki Synestezja a sztuka (red. Aleksandra Rogowska, Julia Kaleńska-Rodzaj).